Electrodeposition of nickel and cobalt on AISI 304 stainless steel plates using the selective coating technique and ethaline as solvent - Baltodano-Obregon, Nicole; Vargas-Gutiérrez, Gregorio (Nexo Revista Científica, 2023)
The electrochemical behaviour of cobalt and nickel chloride hexahydrate in ethaline was investigated by cyclic voltammetry at 30 °C. The results show that the reduction reaction of both elements is quasi reversible and occurs in a single two-electron transfer step. Electrodeposition by the selective coating technique of both elements on AISI 304 stainless steel was performed at -8.7 mA/cm2, 40 °C, and 40 min. The coating was characterised using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoemitted electron spectrometry (XPS). The SEM and TEM images show the presence of a coating with a thickness of about 200 nm and the analysis by XPS confirms the presence of nickel and cobalt on the surface composition of the plate.